PENINGKATAN KETERAMPILAN MENULIS CERPEN DENGAN MENGGUNAKAN MEDIA LAGU SISWA KELAS VIII SMP MUHAMMADIYAH 1 TIDORE KEPULAUAN - Nyo, Julianti; Wahab, Justam; Muharam, Rijal (Jurnal Bilingual, 2020)
This research was conducted with the aim of (1) to find out whether the improvement of short story writing skills using the media song of class VIII Muhammadiyah 1 Middle School Tidore Kepulauan. (2) To find out how to improve short story writing skills by using the media song of class VIII Muhammadiyah Middle School 1 Tidore Kepulauan. The method used in this research is quantitative descriptive method. The population in this study were grade VIII Muhammadiyah 1 Tidore Kepulauan Middle School as many as 25 students while the sample in this study was a total of 25 students as much as 100%. The results of this study are (1) Observation, Indonesian language teachers have taught students with learning material to write short stories through using song media and the teacher has carried out the learning process well in accordance with the Learning Implementation Plan (RPP); (2) Interviews, students interested and happy with learning to write short stories using song media. Media songs are very helpful for them in determining the theme they will make short stories. The theme presented is about friendship that is unique to their world; (3) The initial test (pretest) of students who get very good qualifications (SB) is 3 students by 12%, students who get good qualifications (B) as many as 5 students by 20%, students who get quite good qualifications (CB) as many as 9 students by 36%, students who get poor qualifications (KB) as many as 8 students by 32%, and students who get less qualifications (KS) as many as 0 students at 0%. Has not yet achieved an increase in value; (4) Final test (posttest) of students who get very good qualifications (SB) as many as 8 students by 32%, students who get good qualifications (B) as many as 11 students at 44%, students who get quite good qualifications (CB) as much as 4 students by 16%, students who get poor qualifications (KB) as much as 2 students by 8%, and students who get a score of 1 qualifier less (KS) as many as 0 students at 0%. It means that the use of song can improve students’ scoor in writing short story.